Las Tejanas : 300 years of history - Acosta, Teresa Palomo (Jack and Doris Smothers series in Texas history, life, and culture, 2003)
Since the early 1700s, women of Spanish/Mexican origin or descent have played a central, if often unacknowledged, role in Texas history. Tejanas have been community builders, political and religious leaders, founders of organizations, committed trade unionists, innovative educators, astute businesswomen, experienced professionals, and highly original artists. Giving their achievements the recognition they have long deserved, this book is at once a general history and a celebration of Tejanas' contributions to Texas over three centuries. The authors have gathered and distilled a wide range of information to create this resource. They offer a detailed account of Tejanas' lives in the colonial period and from the Republic of Texas up to 1900. Drawing on the fuller documentation that exists for the 20th century, they also examine many aspects of the modern Tejana experience, including Tejanas' contributions to education, business and the professions, faith and community, politics, and the arts.